ANALISIS PENGARUH KUALITAS PRODUK DAN KEMAMPUAN INOVASI TERHADAP MINAT BELI ULANG DENGAN DAYA TARIK PRODUK SEBAGAI VARIABEL INTERVENING (Studi Pada Parlour Café Semarang) - Diponugroho, Andrawan; Santosa, Suryono Budi (Diponegoro Journal of Management, 2015)
This study aims to explain the impact of product quality and ability to make innovation with product interest as an intervening variable to the repurchase intention as a dependent variable.               The population used in this study is that consumers who had visited Parlour Café Semarang. This research method using a non-probability sampling technique with accidental sampling method. Used as a sample of 100 respondents. Data obtained from the questionnaires were then processed and analyzed using SEM (Structural Equation Modeling) analysis through the AMOS program.            The results showed that the product quality has a positive influence on repurchase intention; product quality has a positive influence on product interest; ability to make innovation has a positive influence on repurchase intention; ability to make innovation has a positive influence on product interest; and product interest have a positive effect on repurchase intention.